Screening of spices for biological activity against Tribolium castaneum (Herbst) adults (University Journal of Zoology, Rajshahi University, 2007)
Key words: Spices, Tribolium castaneum, bioassay, repellent activity Univ. j. zool. Rajshahi Univ. Vol.23, 2004. pp. 65-68